Seroprevalence of SARS-CoV-2 infection among children in Children’s Hospital Zagreb during the initial and second wave of COVID-19 pandemic in Croatia - Lenicek Krleza, Jasna (Biochem Med (Zagreb), 2021)
INTRODUCTION: The study aimed to investigate the prevalence and titres of anti-SARS-CoV-2 antibodies in children treated at the Children’s Hospital Zagreb in the first and the second wave of the COVID-19 pandemic. Statistical significance of difference at two time points was done to determine how restrictive epidemiological measures and exposure of children to COVID-19 infection affect this prevalence in different age groups. MATERIALS AND METHODS: At the first time point (13th to 29th May 2020), 240 samples and in second time point (24th October to 23rd November 2020), 308 serum samples were tested for anti-SARS-CoV-2 antibodies by enzyme-linked immunosorbent assay (ELISA) and electrochemiluminescence immunoassay (ECLIA). Confirmation of results and titre determination was done using virus micro-neutralization test. Subjects were divided according to gender, age and epidemiological history. RESULTS: Seroprevalence of anti-SARS-CoV-2 antibodies differs significantly in two time points (P = 0.010). In first time point 2.9% of seropositive children were determined and in second time point 8.4%. Statistically significant difference (P = 0.007) of seroprevalence between two time points was found only in a group of children aged 11-19 years. At the first time point, all seropositive children were asymptomatic with titre < 8. At the second time point, 69.2% seropositive children were asymptomatic with titre ≥ 8. CONCLUSIONS: The prevalence of anti-SARS-CoV-2 antibodies was significantly lower at the first time point than at the second time point. Values of virus micro-neutralization test showed that low titre in asymptomatic children was not protective at the first time point but in second time point all seropositive children had protective titre of anti-SARS-CoV-2 antibodies.